Analysis of Theme in Discussion Text Written by the Second Year Students of English Department of UNP - Susi Guslita Putri; Rusdi Noor Rosa (Universitas Negeri Padang, 2020)
This research aims at finding out the type of theme dominantly used in the students’ discussion texts written by the second year students of English Department of Universitas Negeri Padang. This study used a descriptive research method. The population of this research was the second year students of English Department of Universitas Negeri Padang. They were selected because they had taken a course on essay writing. The sample was 30 students taken using a cluster random sampling. The data were collected using a test that has been administered twice in order to get the more representative data. The results show that the dominant theme types used in the students’ discussion text are simple unmarked theme (44.61 %), and multiple unmarked theme (42.35 %), and the types of theme least frequently used are simple marked theme (10.14 %), and multiple marked theme (2.90 %). The dominant used of unmarked theme is motivated by the students’ desire to emphasize on the points of the arguments which are indicated by used of nominal groups